Does concurrent pelvic organ prolapse surgery affect outcomes of mid-urethral Sling? A tertiary care experience - Aijaz, Samia; Kashif, Urooj; Chughtai, Novera; Malik, Summera (Journal of the Pakistan Medical Association, 2025)
Objective: To compare the efficacy of mid-urethral sling surgery with and without concurrent pelvic organ prolapse surgery. Method: The retrospective chart review was conducted in May 2022 at the Aga Khan University Hospital, Karachi, and comprised data of female patients who underwent mid-urethral sling surgery either through tension-free vaginal tape or trans obturator tape for stress urinary incontinence between January 2010 and December 2020 and had a complete 12-month follow-up data available. Two groups were formed: Group Ahad mid-urethral sling surgery cases, while Group B, had cases who had concurrent mid-urethral sling and pelvic organ prolapse surgery. Documented parameters, including preoperative data, postoperative complications and satisfaction levels using urogenital distress inventory-6 and incontinence impact questionnaire-7 tools, were compared between the groups. Negative cough stress test was defined as objective cure. Data was analysed using SPSS 19. Results: Of the 345 females, 122(35.4%) were in Group A, with 68(55.7%) aged <50 years. There were 223(64.6%) females in Group B, with 127(57%) aged >50 years(p>0.05). Parity >3 and menopause were significantly higher in Group B (p<0.05), but a positive preoperative cough stress test was high in Group A (p=0.001). At 12-month follow-up, objective and subjective cure rates were not significantly different between the groups (p>0.05). However, at 6 months, urogenital distress inventory-6 scores were significant between the groups (p<0.05). Body mass index was associated with objective failure at 6months. Mid-urethral sling type and the presence of concurrent prolapse surgery had no significant effect (p>0.05). Conclusion: Undergoing simultaneous prolapse surgery and mid-urethral sling surgery had similar risks and success rates as undergoing mid-urethral sling surgery alone. Key Words: Concurrent surgery, Pelvic organ prolapse, Mid-urethral sling, Treatment outcome, Survey and questionnaires.